Leveraging Artificial Intelligence to Transform Leadership Development - Donnie, Adams; Chuah, Kee Man; Pauline, Thompson (Routledge, 2026)
Artiﬁcial intelligence (AI) is transforming the way learning and teaching are implemented in schools (Adams & Chuah, 2022). In particular, the emer-gence of Generative AI (GenAI) technologies, such as ChatGPT, has signiﬁ-cantly impacted the ﬁeld of education in recent years (Chiu, 2024). These AI tools support personalised learning by analysing its users’ performance data and tailoring educational content to individual needs (Hwang et al., 2020). GenAI also enables the creation of original content such as text, images, and videos based on speciﬁc prompts (Adams et al., 2024). One of its unique fea-tures is its ability to produce humanlike conversational dialogue (Chiu, 2024), and it can simulate various roles, such as teachers, administrators, students, or school leaders (Adams & Thompson, 2025). While the implications of AI for teaching and learning have been widely examined (Adams & Chuah, 2022; Levine et al., 2025), its potential to support leadership development has received far less attention in the lit-erature. This gap is particularly noteworthy given that effective leadership is essential for navigating the increasingly complex challenges facing edu-cational organisations (Mincu, 2022). To address this gap, this chapter ex-plores how AI, particularly GenAI can be leveraged to enhance leadership competencies in educational settings, an area that is critically important yet underexplored. This chapter begins by tracing the development of AI and its evolution into today’s transformative force in education. It then examines the intersection of AI and educational leadership, highlighting how aspiring school leaders can harness GenAI technologies as virtual coaching tools. These tools have the po-tential to supplement traditional leadership training by offering personalised, on-demand guidance and simulation-based learning. The chapter concludes by discussing the broader implications of AI for leadership development and offers recommendations for integrating AI into leadership preparation and practice.